Digital Transformation of Municipal Services in Finland - Ahveninen, Tomi (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
Digitalization has been widely adopted by private organizations of all sizes. As customers we are starting to expect a certain level of digital services from businesses and these expectations are evolving to consider the public sector services as well. Moreover, the Finnish municipalities are under pressure to cut costs and make their operation more efficient. This research aims in exploring the field of municipal digitalization in Finland with three main questions to answer: what are the motivations for municipalities for digital service transformation, what the main benefits of this transformation are and what are the challenges for the transformation. The research starts with examining the characteristics of municipal operation and reviewing some of the relevant digital service opportunities. In the empirical part of the research, 11 professionals related to the municipal field were interviewed using a semi-structured interview design. These interviewees were chosen from three important groups for the change: the service provider, municipal administration and municipal employees. The data gained from the interviews was first summarized according to the main topics chosen from the literature and then reflected on the digital services opportunities presented in the research. The motivations discovered in both the service provider and the city of Porvoo interviews were: tightening resources combined with increasing expectations, transparent structuring of information, supporting the shift into mobile and providing new channels for customers to participate. The benefits discovered in all groups were: efficiency, customer experience, transparent structuring of information, reducing manual input and responding to customer needs in service development. The challenges perceived by multiple groups were: change resistance, innovating new with no best practices and defining the scope and new operation model. The results of this research suggest that even with some challenges along the way, digitalization is a likely future for the Finnish public sector. The business case for the transformation is becoming increasingly evident on both municipal- and governmental levels.